An investigation into the physical, physiological and technical demands of small sided games using varying pitch dimensions in Gaelic football. (2nd November 2019) - Mangan, Shane; Collins, Kieran; Burns, Con; O'Neill, Cian
ABSTRACT: Introduction: The purpose of this study was to examine the effects of pitch size on the physical, physiological and technical demands of small-sided games (SSGs) in a sub-elite Gaelic football setting. Methods: Thirty-four sub-elite adult male Gaelic football players completed tailored Gaelic football SSGs on three different pitch sizes (40 x 20 m, 60 x 20 m, 80 x 20 m) in a 4v4 format, resulting in 312 individual player observations over the course of the 2018 season. Results: Participants performed significantly greater high-speed running (>17 km∙h −1 ) (p ≤ 0.001) and sprinting (>22 km∙h −1 ) (p ≤ 0.001) on the 60x20 m pitch compared to the 40x20 m and 80x20 m pitches. Pitch size had only trivial effects on the average heart rate and the peak heart rate recorded in games. Games played on the 40x20 m pitch resulted in more scores per team (p = 0.062; η 2 = 0.071), no-score entries (p = 0.075; η 2 = 0.067) and possessions per team (p = 0.015; η 2 = 0.106), while ball-in-play percentage was moderately higher (p = 0.040; η 2 = 0.082) on the 80x20 m pitch. Conclusion: Coaches should consider pitch size and the associated effects on physical and technical demands when planning training games, with specific reference to the stated objectives of each respective session.